Chromatin Decondensation and T Cell Hyperresponsiveness in Diabetes-Associated Hyperglycemia - Martinez, Nuria (J Immunol, 2014)
Diabetes is linked to increased inflammation and susceptibility to certain infectious diseases including tuberculosis (TB). We previously reported that aerosol TB in mice with chronic (≥12 wk) hyperglycemia features increased bacterial load, over-production of several cytokines and increased immune pathology compared to normoglycemic controls. A similar phenotype exists in human diabetics with TB. The mechanisms of increased T cell activation in diabetes are unknown. In the current study, we tested the hypothesis that hyperglycemia modifies the intrinsic responsiveness of naïve T cells to TCR stimulation. Purified T cells from chronically hyperglycemic (HG) mice produced higher levels of Th1, Th2 and Th17 cytokines and proliferated more than T cells from normoglycemic controls after anti-CD3e or antigen stimulation. In this way, naïve T cells from HG mice resembled antigen-experienced cells although CD44 expression was not increased. Chromatin decondensation, another characteristic of antigen-experienced T cells, was increased in naïve T cells from HG mice. That phenotype depended on expression of the receptor for advanced glycation end products (RAGE) and could be reversed by inhibiting p38 MAPK. Chromatin decondensation and hyperresponsiveness to TCR stimulation persisted following transfer of T cells from HG mice into normoglycemic mice. We propose that chronic hyperglycemia causes RAGE-mediated epigenetic modification of naïve T cells leading to p38 MAPK-dependent chromatin decondensation. This pre-activation state facilitates transcription factor access to DNA, increasing cytokine production and proliferation following TCR stimulation. This mechanism may contribute to pathological inflammation associated with diabetes and might offer a novel therapeutic target.